2021
DOI: 10.1186/s12886-021-02158-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness in multiple sclerosis with and without optic neuritis: a four-year follow-up study from Oman

Abstract: Background Multiple sclerosis (MS) is an autoimmune disease that attacks the central nervous system, with optic neuritis (ON) being a common early manifestation. Retinal nerve fiber layer (RNFL) thickness may be a biomarker of neuroaxonal damage in MS patients. We sought to evaluate changes in RNFL thickness over 4 years in Omani MS patients with or without ON in comparison to a healthy control group. Methods This retrospective case-control study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In addition, retinal degeneration is also reported in other neurodegenerative diseases, traditionally affecting other CNS regions, such as multiple sclerosis (including in the absence of associated optic neuritis) [ 106 , 107 , 108 ], Alzheimer’s [ 109 , 110 ], and Parkinson’s [ 111 , 112 ], diseases, giving rise to the concept that the retina can serve as ‘diagnostic window into the brain’ and giving insight into neurodegenerative processes occurring elsewhere [ 113 ]. In humans, thinning of the retinal nerve fibre layer (RNFL) containing RGC axons has been used as a diagnostic indicator of retinal, and particularly RGC, degeneration (as well as testing of neuroprotective therapies) since this region is particularly vulnerable in glaucoma [ 114 ], diabetic retinopathy [ 115 ], retinal ischemia [ 116 ] and in optic neuritis [ 104 ] as well as in multiple sclerosis [ 117 ], Alzheimer’s [ 118 , 119 ] and Parkinson’s [ 120 , 121 ] diseases.…”
Section: Vulnerability Of the Retina And Rgcs To Diseasementioning
confidence: 99%
“…In addition, retinal degeneration is also reported in other neurodegenerative diseases, traditionally affecting other CNS regions, such as multiple sclerosis (including in the absence of associated optic neuritis) [ 106 , 107 , 108 ], Alzheimer’s [ 109 , 110 ], and Parkinson’s [ 111 , 112 ], diseases, giving rise to the concept that the retina can serve as ‘diagnostic window into the brain’ and giving insight into neurodegenerative processes occurring elsewhere [ 113 ]. In humans, thinning of the retinal nerve fibre layer (RNFL) containing RGC axons has been used as a diagnostic indicator of retinal, and particularly RGC, degeneration (as well as testing of neuroprotective therapies) since this region is particularly vulnerable in glaucoma [ 114 ], diabetic retinopathy [ 115 ], retinal ischemia [ 116 ] and in optic neuritis [ 104 ] as well as in multiple sclerosis [ 117 ], Alzheimer’s [ 118 , 119 ] and Parkinson’s [ 120 , 121 ] diseases.…”
Section: Vulnerability Of the Retina And Rgcs To Diseasementioning
confidence: 99%
“…As the optic nerve is an extension of the CNS, previous studies have hypothesized reduced RNFL thickness may be a biomarker for axonal loss in the CNS even in the absence of clinical optic neuritis 63,64 . However, more recent cross‐sectional and longitudinal studies showed no statistically significant difference in RNFL thinning in MS patients without a prior history of optic neuritis as compared to controls 65,66 . Although histopathology of human optic neuritis is lacking, there is evidence from a guinea pig model of autoimmune optic neuritis demonstrating swollen axons displaced into the peripapillary retinal tissue forming an S‐shaped bulge resembling PHOMS 16 .…”
Section: Diseases Associated With Phomsmentioning
confidence: 99%
“…In the present study, the rates of RNFL and GCL-IPL thinning in non-ON BMS were −0.20 ± 0.27 and −0.19 ± 0.15 μm/year, mean ± SE, respectively, in agreement with results from earlier extrapolated rates for RNFL and GCL-IPL, where thickness loss was −0.11 ± 0.27 and −0.24 ± 0.24 μm/year, respectively [ 20 ]. The earlier study also reported a thinning rate of 0.54 ± 0.24 μm/year for RNFL in RR-MS; in other studies, the reported rate of loss of RNFL thickness in MS differed from about 0.9 µm/year [ 38 ] to 2.4 µm/year [ 39 ].…”
Section: Discussionmentioning
confidence: 90%